An In Vitro Evaluation of the Remineralizing Efficacy of Two concentrations of Silica Doped Nanohydroxyapatite on Bleached Enamel - S, Sajjan Girija; T, Rishitha; P, Bhupathi Arun; Varma, K Madhu; Kumar, Pulidindi Anil; CH, Rajashekar; Kumar, M Sita Rama; Durga, I. Sai Lakshmi (Malaysian Journal of Medicine and Health Sciences, 2022)
Introduction: Vital bleaching of teeth is associated with mineral loss and surface roughness leading to hypersensitivity. Aesthetic restorations are recommended after one week. Search is on for a suitable remineralizing material, which helps in instant adhesive bonding. Hence objective of the study is to evaluate the remineralizing efficacy of two concentrations of Silica doped Nanohydroxyapatite on bleached enamel. Methods: Enamel surfaces of 30 extracted human central incisors were divided into Part A: Unbleached enamel, Part B: Bleached enamel, Part C: Remineralized enamel. The samples were randomly divided into, Group 1: MI Paste Plus (Recaldent, USA), Group 2 and 3 for application of Dentin bonding agents (Tetric- n-bond, Ivoclar, Vivadent) mixed 0.2% and 0.8% Silica doped Nanohydroxyapatite (Sigma Aldrich, Bangalore, India). Post bleaching remineralizing agents were applied on part C. Surface roughness was evaluated with contact stylus profilometer and mineral content was evaluated with Energy dispersive X-Ray spectroscopy for three parts. Data were analysed using ANOVA and Post Hoc Tukey test with p ≤ 0.05. Results: Surface roughness values (Ra) were increased, and mineral loss (Ca:P) was observed after bleaching. After application of remineralizing agents, surface roughness was decreased with no significant value (p > 0.05) and a significant increase in mineral content of all three groups with a p < 0.05 was observed. Conclusion: Application of dentin bonding agent mixed with Silica doped Nanohydroxyapatite decreased surface roughness and improved remineralization of bleached enamel.